Infant Safety In Incubator Care In The Perinatology Room - Supriatin Supriatin; Anisa Oktiawati; Jumrotun Ni'mah (International Journal of Health Sciences, 2026)
The safety of premature and high-risk infants in the perinatology ward is a top priority in neonatal health care. The use of incubators as a thermoregulation aid and environmental protection plays a crucial role in maintaining the infant's physiological stability. However, improper use of incubators can lead to risks such as hyperthermia, hypothermia, infection, and respiratory distress. This study aims to analyze the safety aspects of infants in incubator care in the perinatology ward. The study used a descriptive analytical design with an observational approach. The study sample consisted of 50 infants treated using incubators. Data were collected through observation of care procedures, monitoring of physiological parameters, and evaluation of health workers' compliance with standard operating procedures (SOPs). The results showed that the majority of incubator care met standards, but several safety risks were still found related to temperature regulation and sterilization procedures. It was concluded that the implementation of SOPs and strict monitoring significantly influenced the safety of infants in incubator care.